Look to the stars—Is there anything that public health and rehabilitation can learn from elite sports? - Millet, Grégoire P.; Chamari, Karim (Frontiers in Sports and Active Living, 2023)
At first glance, fine-tuned individualized prescriptions or exercise monitoring for elite athletes may appear disconnected from general public health or rehabilitation concerns/recommendations. However, beyond the obvious differences in absolute physiological characteristics or training loads, we argue that there are at least 22 topics where public health and rehabilitation can benefit from methods or innovations originated or developed in elite sports. In this opinion letter, we state that improved strategies leading to larger positive outcomes may be obtained in the following areas: A: Exercise prescription: 1. Submaximal cardiovascular assessment; 2. Individualization of exercise intensity; 3. Prescribed interval training based on VO2 kinetics; 4. Submaximal strength assessment; 5. Non-invasive assessment of diffusive and convective components of O2 transport; 6. Non-invasive assessment of muscle oxidative capacity; 7. Non-invasive assessment of muscle structural properties. B: Monitoring of fatigue and adaptations: 8. Multidisciplinary approach; 9. Specific exercise wearables; 10. Non-invasive cardiovascular monitoring; 11. Coping strategies from extreme sports. C: Optimizing exercise dose‒response to physical activity: 12. Integration of environmental conditions; 13. Concurrent endurance and strength training; 14. Weight-reduced load; 15. Vascular occlusion; 16. Neuromuscular electrical stimulation; 17. Transcranial direct current stimulation; 18. Specific responses in women; 19. Exercise training quantification; 20. Predictive models; 21. Technological innovations in mobility; 22. Ethical considerations. Many investigations have been undertaken in the expanding areas of the preventive or therapeutic benefits of exercise. The above-mentioned methods currently performed at the top performance level provide many underexplored but promising strategies that are worth further investigation. We discuss the main opportunities and obstacles to transferring knowledge, methods, and devices from sports, exercise science and medicine related to elite performance (e.g., exercise physiology, sports biomechanics, sports nutrition, sports psychology) to general or clinical populations.